The discrepancies in parent and teacher reports of children’s behavioral inhibition provide domain-specific information about psychopathology and parenting - Sulyok, Róza Sára; Miklósi, Mónika; Kárpáti, Noémi; Györe, Szandra; Szabó, Brigitta (Frontiers in Psychiatry, 2024)
IntroductionBehavioral inhibition is a temperamental factor that increases the risk of internalizing disorders. Therefore, the identification of highly inhibited children is of great importance. However, informant discrepancies make this process difficult. In a cluster analytic approach, we aimed to use both parent and teacher reports of behavioral inhibition in order to gain a more detailed picture about children’s behavioral inhibition in different contexts and to characterize highly inhibited children.MethodsParents and teachers of 318 preschool children completed a questionnaire, which included the Behavioral Inhibition Questionnaire (BIQ) and the Strengths and Difficulties Questionnaire (SDQ). Parents also reported their parenting behavior on the Multidimensional Assessment of Parenting Questionnaire (MAPS). A two-step cluster analysis was conducted on BIQ parent and teacher reports, and the resulting clusters were compared on the SDQ externalizing and internalizing subscales. Multinomial logistic regression analyses were conducted separately for girls and boys to predict cluster membership based on the MAPS hostility, lax control and physical control subscales.ResultsFour clusters were identified, labelled as medium-low (ML), low-elevated (LE), elevated-elevated (EE) and high-high (HH), based on the levels of BIQ parent and teacher reports, respectively. In the HH cluster, mean scores of the SDQ internalizing subscales as reported by parents and teachers were significantly higher, and in boys but not in girls, mean scores of the SDQ externalizing subscale as reported by teachers were lower than in the other clusters. High levels of hostility predicted group membership of HH compared to LE and EE in both genders. Furthermore, in boys, lax control and physical control were also found to be significant when comparing HH to EE and LE, respectively.DiscussionOur results suggest that the joint use of parent and teacher reports on behavioral inhibition may increase the ability to identify highly inhibited children at risk of developing internalizing disorders and add to our understanding of the underpinnings of children’s inhibited behavior in different contexts.